(untitled) (Physical Education, Health and Social Sciences, 2025)
The soul of literature is poetry. In the discipline of translation studies, which is a very ancient field known to humans, translating poetry is the most difficult process in all types of translation. The current research is held to see, that on what extent AI is reliable as a translating tool in comparison to human translation in term of Literary text. It includes the most common AI tool used by students which is ChatGPT-4 and traditional translating tool (Google Translator). The aim of this paper is to identify the efficiency of AI in the field of translation studies i.e. especially in poetry; by using one of the poems of Allama Iqbal i.e. Ahl-e-Hunar SY. The poem undergoes into firstly self-translation and secondly into machine (AI) translation and it was examined that there are very minor differences between the literal and semantic meanings of source text and the targeted text. After a critical examination of translations, it is revealed that the AI actually surpasses the humanized translation in term of literary text.